Development of Practicum Worksheet on Project Based Learning on Environmental Pollution Material - Santoso, Luhur Pujo; Nurwahyunani, Atip; Ulfah, Maria (Unnes Science Education Journal, 2023)
Problems that are often experienced in learning Environment Pollution material is the lack of participation of learners in the formation his knowledge, this is due to the learning provided only limited to theory without utilizing laboratory facilities for activities practicum. In addition, the teaching materials used are less able to hook material with contextual phenomena in everyday life, so that lack of opportunities for learners to conduct investigations. This research aims to develop practicum worksheet on Project Based Learning on environmental pollution material. The research method used is Research and Development (R&D). The preparation of practicum worksheet uses the ADDIE model, but in this study only focuses on the ADD (Analysis, Design, and Development) stage. Practicum worksheet design that has been prepared before being tested is measured for quality through validation activities by material experts and media experts. Validation was carried out by 2 material experts and 2 media experts, in this case lecturers from PGRI Semarang University. The final average score of validation results by material experts was 92.36% and media experts was 90.33%. This value included in the very valid category, so that the practicum worksheet that has been prepared is suitable for use in learning Environmental Pollution material.